Biodiversity and community structures across the Magellan seamounts and abyssal plains in the western Pacific Ocean revealed by environmental DNA metabarcoding analysis - Kim, Eun-Bi; Ju, Se-Jong; Suh, Yeon Jee (Frontiers in Marine Science, 2024)
Seamounts within deep-sea ecosystems are recognized as biodiversity hotspots, yet they are increasingly threatened by anthropogenic activities such as overfishing, resource exploitation, and climate change. To establish environmental baseline data and assess the impacts of current or future anthropogenic activities, we conducted environmental DNA (eDNA) metabarcoding analyses to comprehensively characterize prokaryotic and eukaryotic diversity across various water depths of the Magellan seamounts and the adjacent abyssal plains. Metabarcoding analysis revealed higher richness and diversity in both prokaryotic and eukaryotic communities within the seamounts compared to the abyssal plains. Overall, the analysis identified 9,068 prokaryotic amplicon sequence variants (ASVs), representing 39 phyla and 47 classes. Similarly, 4,569 eukaryotic ASVs were identified, spanning 34 phyla and 93 classes. Furthermore, our results revealed distinct community structures between the seamounts and abyssal plains, with turnover across different water depths. These findings are crucial as they indicate the unique ecological roles and potential vulnerability of seamount communities, emphasizing the need for targeted conservation strategies. Our study underscores the importance of conducting comprehensive long-term environmental assessments of the impacts of anthropogenic activities on seamount ecosystems and highlights the potential of eDNA metabarcoding as a powerful tool for guiding conservation and management efforts in remote and challenging marine environments.